A case of intravascular large B-cell lymphoma of lung presenting with progressive multiple nodules on chest computed tomography. (2017) - Bae, Hyun Jin; Chon, Gyu Rak; Kim, Dae Jung; Lee, Sun Hun; Ahn, Jin-Young
Abstract: A 71-year-old man was admitted to our hospital for dyspnea, which had worsened over a period of more than six months. He was previously diagnosed as having cryptogenic organizing pneumonia, and was treated with steroids in another hospital. He had complained of worsening dyspnea, despite the treatment. We performed video-assisted thoracoscopic surgery because of the high level of lactate dehydrogenase and inconsistency of the usual interstitial pneumonia pattern. Pathologic specimens showed atypical lymphocytes confined to the pulmonary capillaries. On immunohistochemical staining, tumor cells were found positive for CD20, without the T-cell marker. It was consistent with findings of intravascular large B-cell lymphoma. We report this case, which presented with progressive multiple nodules on chest computed tomography.